Higher Matrix Stiffness Upregulates Osteopontin Expression in Hepatocellular Carcinoma Cells Mediated by Integrin β1/GSK3β/β-Catenin Signaling Pathway - You, Yang; Zheng, Qiongdan; Dong, Yinying; Wang, Yaohui; Zhang, Lan; Xue, Tongchun; Xie, Xiaoying; Hu, Chao; Wang, Zhiming; Chen, Rongxin; Wang, Yanhong; Cui, Jiefeng; et al. (PloS one, 2015)
Increased stromal stiffness is associated with hepatocellular carcinoma (HCC) development and progression. However, the molecular mechanism by which matrix stiffness stimuli modulate HCC progress is largely unknown. In this study, we explored whether matrix stiffness-mediated effects on osteopontin (OPN) expression occur in HCC cells. We used a previously reported in vitro culture system with tunable matrix stiffness and found that OPN expression was remarkably upregulated in HCC cells with increasing matrix stiffness. Furthermore, the phosphorylation level of GSK3β and the expression of nuclear β-catenin were also elevated, indicating that GSK3β/β-catenin pathway might be involved in OPN regulation. Knock-down analysis of integrin β1 showed that OPN expression and p-GSK3β level were downregulated in HCC cells grown on high stiffness substrate compared with controls. Simultaneously, inhibition of GSK-3β led to accumulation of β-catenin in the cytoplasm and its enhanced nuclear translocation, further triggered the rescue of OPN expression, suggesting that the integrin β1/GSK-3β/β-catenin pathway is specifically activated for matrix stiffness-mediated OPN upregulation in HCC cells. Tissue microarray analysis confirmed that OPN expression was positively correlated with the expression of LOX and COL1. Taken together, high matrix stiffness upregulated OPN expression in HCC cells via the integrin β1/GSK-3β/β-catenin signaling pathway. It highlights a new insight into a pathway involving physical mechanical signal and biochemical signal molecules which contributes to OPN expression in HCC cells.